Photographic albums: self-representation and memory storage praxis in society - Hermanovska, Stella (IJRDO- Journal of Educational Research, 2017)
Albums are one of the most common types of memory storage. The objective of the abstract was toexplore album phenomenon that has left an impression on society. The albums affected performedrituals in society, ranging from going to studio or taking photographs, album purchase andphotography collecting and showing album to others. The album’s popularity is due to theavailability of photography and its high distribution, as well as to scientific development, lifestyleand values. The album passed science achievement results: photography invention, the processdevelopment, the industrial revolution, which opened the way for the mass production goods moveto market. The album was convenient and a visually aesthetic solution that buyers willingly boughtand manufacturers, offered in the growing diversity of design, since nineteenth-century albumsbecame a mass product. The content and typology of albums changed: at the beginning, society’spurpose was self-representation, but later, storytelling